A new theory on GABA and Calcitonin Gene-Related Peptide involvement in Mal de Debarquement Syndrome predisposition factors and pathophysiology. (November 2018) - Mucci, Viviana; Jacquemyn, Yves; Van Ombergen, Angelique; Van de Heyning, Paul H.; Browne, Cherylea J.
Abstract: Introduction: Mal de Debarquement Syndrome (MdDS) is a condition characterized by a sensation of motion in the absence of a stimulus, which presents with two subtypes depending on the onset: Motion-Triggered, and Spontaneous or Non-Motion Triggered. MdDS predominantly affects women around 40–50 years of age and a high number of patients report associated disorders, such as migraine and depression. The pathophysiology of MdDS is unclear, as is whether there are predisposing factors that make individuals more vulnerable to developing the condition. Hormonal changes in women similarly to what observed in migraineous patients, as well as depression disorder, have been examined as potential key factors for developing MdDS. Studies on migraine and depression have revealed correlations with hormonal fluctuations in females as well as aberrant levels of some key neurotransmitters such as Gamma-Aminobutyric Acid (GABA) and inflammatory neuropeptides like Calcitonin Gene-Related Peptide (CGRP). Consequently, this manuscript aims to propose a new hypothesis on the predisposing factors for MdDS and a new concept that could contribute to the understanding of its pathophysiology. New hypothesis: Recent findings have demonstrated a role for hormonal influences in MdDS patients, similar to previous observations in patients with depression and migraine. We hypothesize the involvement of gonadal hormones and aberrant neurotransmitter levels, including the GABAergic and serotonergic systems, in MdDS pathophysiology. Our theory is that certain individuals are more vulnerable to develop MdDS during specific gonadal hormonal phases. Furthermore, we hypothesize that it may be possible to identify these individuals by measurement of an existing imbalance of these neurotransmitters or inflammatory neuropeptides like CGRP. Further evaluation of the hypothesis: According to one theory, MdDS is considered as a maladaptation of the Vestibular Ocular Reflex (VOR) and velocity storage. When considering this theory, it is essential to highlight that the brainstem nuclei involved in the VOR and the velocity storage include GABAb sensitive neurons, which appear to produce inhibitory control of velocity storage. Responses of these GABAb sensitive neurons are also modulated by CGRP. Thus an alteration of the GABAergic network by imbalances of inhibitory neurotransmitters or CGRP could influence signal integration in the velocity storage system and therefore be directly involved in MdDS pathophysiology. Consequence of the hypothesis and future studies: A hormonal and neurotransmitter imbalance may act to predispose individuals in developing MdDS. Future studies should focus on the hormonal influences on neurotransmitters (e.g. GABA) and on the trial of CGRP antagonist drugs for the treatment of MdDS patients.